The emerging role of clinical informatics fellows in service learning during the COVID-19 pandemic. (4th November 2020) - Subash, Meera; Sakumoto, Matthew; Bass, Jeremy; Hong, Peter; Muniyappa, Anoop; Pierce, Logan; Purmal, Colin; Ramaswamy, Priya; Sono, Reiri; Uptegraft, Colby; Feinstein, David; Khanna, Raman
Abstract: Objective: The study sought to describe the contributions of clinical informatics (CI) fellows to their institutions' coronavirus disease 2019 (COVID-19) response. Materials and Methods: We designed a survey to capture key domains of health informatics and perceptions regarding fellows' application of their CI skills. We also conducted detailed interviews with select fellows and described their specific projects in a brief case series. Results: Forty-one of the 99 CI fellows responded to our survey. Seventy-five percent agreed that they were "able to apply clinical informatics training and interest to the COVID-19 response." The most common project types were telemedicine (63%), reporting and analytics (49%), and electronic health record builds and governance (32%). Telehealth projects included training providers on existing telehealth tools, building entirely new virtual clinics for video triage of COVID-19 patients, and pioneering workflows and implementation of brand-new emergency department and inpatient video visit types. Analytics projects included reports and dashboards for institutional leadership, as well as developing digital contact tracing tools. For electronic health record builds, fellows directly contributed to note templates with embedded screening and testing guidance, adding COVID-19 tests to order sets, and validating clinical triage workflows. Discussion: Fellows were engaged in projects that span the breadth of the CI specialty and were able to make system-wide contributions in line with their educational milestones. Conclusions: CI fellows contributed meaningfully and rapidly to their institutions' response to the COVID-19 pandemic.